International regulation and treatment of trade finance: What are the issues? - Marc Auboin (World Trade Organization (WTO), 2010)
The paper discusses a number of issues related to the treatment of trade credit internationally, a priori (treatment by banking regulators) and a posteriori (treatment by debtors and creditors in the case of default), which are currently of interest to the trade finance community, in particular the traditional providers of trade credit and guarantees, such as banks, export credit agencies, regional development banks, and multilateral agencies. The paper does not deal with the specific issue of regulation of official insured-export credit, under the OECD Arrangement, which is a specific matter left out of this analysis. Traditionally, trade finance has received preferred treatment on the part of national and international regulators, as well as by international financial agencies in the treatment of trade finance claims, on grounds that trade finance was one of the safest, most collateralized, and self-liquidating forms of trade finance. Preferred treatment of trade finance also reflects the systemic importance of trade, as in sovereign or private defaults a priority is to treat expeditiously trade lines of credits to allow for such credit to be restored and trade to flow again. It is not only a matter of urgency for essential imports to be financed, but also a pre-condition for economic recovery, as the resumption of trade is necessary for ailing countries to restore balance of payments equilibrium. The relatively favourable treatment received by trade finance was reflected in the moderate rate of capitalization for cross-border trade credit in the form of letters of credit and similar securitized instruments under the Basel I regulatory framework, put in place in the late 1980s and early 1990s. However, as the banking and regulatory communities moved towards internal-rating based and risk-weighted assets systems under the successor Basel II framework, a number of complaints emerged with respect to the treatment of trade credit particularly in periods of crisis. Issues of pro-cyclicality, maturity structure and country risk have been discussed at some length in various fora, including in the WTO at the initiative of Members. Part of the issue was that Basel II regulation was designed and implemented in a manner that, in periods of banking retrenchment, seemed to have affected the supply of trade credit more than other potentially more risky forms of lending. With the collapse of trade in late 2008 and early 2009, the regulatory treatment of trade credit under Basel II clearly became an issue and was discussed by professional banking organizations, regulators and international financial institutions. A sentence made its headway into the communiqué of G-20 Leaders in London in April 2009, calling upon regulators to exercise some flexibility in the application of Basel II rules, in support of trade finance. As the issue of removing the obstacles to the supply of trade finance spread became part of the public debate, discussions with respect to the regulatory treatment of trade finance in the context of the making of Basel III rules are now raising political attention.
Keywords: E44; F13; F34; F36; O19; G21; G32; 330; trade financing; cooperation with international financial institutions; coherence; G-20; financial crisis; Außenhandelsfinanzierung; Internationale Kreditvergabe; Finanzmarktkrise; G-20-Staaten